Self-Reported Physical Activity and Aerobic Endurance Among Female Students of Pavol Jozef Šafárik University in Košice, Slovakia - Agata Horbacz; Mária Majherová; Richard Melichar; Ján Junger (Jan Długosz University in Częstochowa, 2024)
One of the easiest ways to improve everyone's physical and mental health is to choose appropriate physical activity (PA). Its general decline in recent decades has triggered an increase in civilisation-related diseases. Female college students neglect PA more than males. We compared the PA of female undergraduates at the University of P.J. Šafárik in Košice (UPJŠ) to their actual aerobic endurance based on our research. The study comprised 268 female students from four UPJŠ faculties. PA data were gathered using a short version of the International Physical Activity Questionnaire (IPAQ). Aerobic endurance capacity was determined using the results of a 20m beep-test, which was then converted to estimated VO2 max values. The results were comparable to other studies when converted to MET-min/week, but undergraduate students' self-reported PA did not differ between faculties. A correlation exists between total (r = 0.24; p <0.05) and vigorous (r = 0.34; p <0.05) PA and 20m beep-test aerobic endurance. The level of PA among female UPJŠ students is in line with that observed in other studies following pandemic prevention measures. However, its lower intensity may affect aerobic performance. Future goals include increasing female students' interest in moderate- and high-intensity PA to improve aerobic endurance and health.